Convoluted Fractional C-Semigroups and Fractional Abstract Cauchy Problems - Zhan-Dong Mei; Ji-Gen Peng; Jing-Huai Gao (Abstract and Applied Analysis)
We present the notion of convoluted fractional C-semigroup, which is the generalization of convoluted C-semigroup in the Banach space setting. We present two equivalent functional equations associated with convoluted fractional C-semigroup. Moreover, the well-posedness of the corresponding fractional abstract Cauchy problems is studied.